Android-Based Car Tire Pressure Monitoring System - Aman, Andryanto; Randy Angriawan; Zulfikar; Erwin Gatot Amiruddin (Ceddi Journal of Information System and Technology (JST), 2022)
Inadequate tire pressure is a significant factor that accelerates tire damage and increases the risk of traffic accidents. This often occurs because tire pressure checking is still done manually with simple tools, which is not only inefficient but also prone to measurement errors. Therefore, a system capable of monitoring vehicle tire pressure automatically and in real-time is needed. This research aims to design and implement an Android-based car tire pressure monitoring system. Research data was obtained through field research and literature review. At the same time, system requirements analysis was conducted using the PIECES method (Performance, Information/Data, Economic, Control/Security, Efficiency, and Service) to ensure the quality, effectiveness, and safety of the resulting system. The results show that the developed system is capable of detecting tire pressure with high accuracy and displaying this information directly through an Android application. This feature allows users to take preventative action more quickly when abnormal pressure is detected, thereby reducing the risk of accidents and tire damage. Furthermore, the implementation of this system has been proven to improve vehicle maintenance efficiency by eliminating the need for routine manual checks. This innovation offers significant benefits not only to middle-class vehicle users but also to the upper class, who require practical and modern solutions for maintaining safe driving. Therefore, this research has a tangible impact in supporting transportation safety, reducing maintenance costs, and contributing to the development of future Internet of Things (IoT)-based automotive technology.